PREVALENT POSITIONED SLANG WORD TAPESTRY IN - Marwito Wihadi; Shaffa Putri Pratiwi; Wulan Rahmatunnisa (Universitas Widyatama, 2020)
This research draws on a sociolinguistics study of slang word commonly encountered in social media aimed to conduct to identify the types and analyze the function of slang. The data are elicited from natural conversation among the members of Potatoes Crew WhatsApp Group. This research uses a case study qualitative method for in-depth analysis so as to understand the activity and the process of their using slang words. The result of this research identifies seventy slang words or phrases. The classification of categories of slang types are fresh and creative (41,4%), flippant (0%), imitative (20%), acronym (18,6%), clipping (20%). Regarding the slang functions, the variety of coverage are to address (8,6%), to reveal anger (7,15%), to show intimacy (7,15%), to form intimate atmosphere (0%), to humiliate (20%) and to initiate relax conversation (57,1%). Fresh and creative slang type is the most preponderantly used by the members while the function of slang word mostly found is to initiate relax conversation. It is concluded that the slang word type with its function is substantially determined by the tenors of the members. It is highly recommended that the deeper analysis in diverse community relative to gender-based emphasis shall be pursued.